Cicatrizing effect of Copaifera officinalis (copaiba) oil in patients with peptic ulcer - Arroyo-Acevedo, Jorge (2011)
Objectives: To determine the cicatrizing effect of Copaifera officinalis’ stem bark copaiba oil compared with omeprazole 20 mg in patients with diagnosis of peptic ulcer. Design: Experimental, comparative, phase II, randomized, double-blind, parallel-group clinical trial. Setting: Clinical Investigation Institute, Faculty of Medicine, Universidad Nacional Mayor de San Marcos, Lima, Peru. Participants: Patients with diagnosis of peptic ulcer. Interventions: Clinical diagnosis of peptic ulcer was done by endoscopy as well as pre and post treatment evaluation following administration of copaiba oil formulated capsules (80 mg and 120 mg). Sixty patients enrolled voluntarily to the study and signed informed consent as approved by the Institutional Review Board. Patients were randomly distributed in three groups of 20 cases each according to arrival order; the first and second group received respectively copaiba oil 80 mg and 120 mg capsules, and the third group omeprazole 20 mg, fasting, once daily in the morning, half hour before breakfast. Data was evaluated through multivariate techniques, considering p<0.05 as statistically significant. Main outcome measures: Percentage of patients healing their ulcer. Results: Peptic ulcer cicatrized in 65% and 75% respectively versus 100% in the omeprazole group, without significant adverse effects. Two patients presented nausea and three epigastric pain. Conclusions: Patients with peptic ulcer treated with copaiba oil capsules showed ulcer scarring in 65% to 75% and without significant adverse effects.